PENYULUHAN PENCEGAHAN WABAH PENYAKIT MENULAR COVID 19 DI LINGKUNGAN RT 02 RW 01 DESA NGABAR KECAMATAN JETIS MOJOKERTO - Sutikno, Sutikno (Universitas Respati Yogyakarta, 2021)
At the end of 2019 in December 1 in the Bamboo Curtain Country, to be precise in Hubei province, Wuhan city, a different type of Corona virus appeared called SARS-Cov-2 or better known as Covid 19. In the northern part of the city of Mojokerto which is located On the border of Mojokerto and Gresik there is an area of Jetis sub-district, to be precise, Ngabar village with an area of 3.25 km2 with a population of 6,120 in 2016 with a primary education level of 40% Junior High School and the equivalent 30% Senior High School 20% College level both S1 and S2 5% and the other 5% non-productive age. And the jobs of villagers are farmers, traders, teachers, businessmen, factory employees, lecturers. Corona virus is a virus that can cause serious and mild illness with signs of fever above 380C, coughing, shortness of breath, which is treated in a hospital. knowledge, socialization about the dangers of infectious diseases and low public awareness which causes people to be ignorant, it is hoped that the public will be more aware that infectious disease outbreaks will soon disappear. The problems that exist in society make me aware of the importance of maintaining a healthy lifestyle, preventing death and breaking the chain of transmission of Covid 19. It is important to provide education to prevent infectious diseases starting from the family environment, starting from washing hands regularly, wearing masks when leaving the house, maintaining a minimum distance of 1 meter, sneezing ethics when in public places, how to apply cleanliness in places of worship. Extension methods using demonstration or direct modelsKeywords, Covid 19, Â contagious, knowledge